The role of interleukin-37 and interleukin-38 in the development and remission of autism spectrum disorder: a comprehensive review of neuroinflammatory mechanisms and potential therapeutic implications - Al Rasbi, Zakeya; Orsud, Hiba; Zoughbor, Sumaya Hasan; Hajar, Malak; Mahboob, Abdulla; Sadek, Bassem (Frontiers in Immunology, 2025)
Autism spectrum disorder (ASD) is a complicated neurodevelopmental syndrome characterized by abnormalities in social communication, lack of interests, and repetitive behaviors. Increasing evidence from recent studies indicates that neuroinflammation and immunological dysregulation play essential roles in the pathogenesis of ASD. This review consolidates current knowledge on two anti-inflammatory cytokines of the IL-1 family, interleukin-38 (IL-38) and interleukin-37 (IL-37), which have recently emerged as essential modulators of neuroimmune mechanisms in ASD, highlighting their emerging roles in ASD pathogenesis and therapeutic potential. Based on a combination of clinical and experimental findings, IL-38 has been reported to exert anti-inflammatory effects by suppressing microglial activation and reducing the release of pro-inflammatory cytokines. Consequently, modulation of IL-38/IL-36R signaling axis appears to represent a crucial mechanism regulating neuroinflammation in brain regions relevant to autism. On the other hand, studies indicate that IL-37 exhibits a consistent upregulation in the brain tissues associated with ASD, functioning via IL-37/IL-18Rα/IL-1R8 pathway, where it inhibits cytokine synthesis, alters microglial polarization, and affects communication along the gut–brain axis. While these findings establish IL-38 and IL-37 as possible biomarkers for ASD diagnosis and treatment targets, these investigations are still emerging. This review establishes the foundation for understanding the growing importance of cytokines and highlights the requirement for further research to clarify their roles and to formulate potential treatment approaches for ASD.